Eye tracking based human computer interaction: Applications and their uses - Chandra, Sushil; Sharma, Greeshma; Malhotra, Saloni; Jha, Devendra; Mittal, Alok Prakash (2015 International Conference on Man and Machine Interfacing (MAMI), 2015)
With the evolution of Eye Tracking from a concept to reality, it is being explored scientifically these days in Human Computer Interaction in order to record the eye movements to determine the gaze direction, position of a user on the screen at a given time and the sequence of their movement. The threefold objective of this paper include introducing the reader to the key aspects and issues of eye-movement technology, practical guidance for developing an Eye tracking application, and various opportunities and underlying challenges to develop (Man and Machine Interfacing) MAMI systems using Eye tracking. We have uniquely integrated The Eye Tribe with Unity5.1.1 and through an experiment, we have also inferred that a subject with and without bifocal glasses show relatively similar fixation results if they have correct vision but the results differ with small error if the eye is corrected using lenses. Another experiment using Eye Tribe shows that gaze input requires less time as compared to the mouse input.